A PROBABILISTIC APPROACH FOR ESTIMATING RETURN PERIODS OF EXTREME ANNUAL RAINFALL IN DIFFERENT CITIES OF KHYBER PAKHTUNKHWA (KPK), PAKISTAN - Ali, M.; Iqbal, M. J. (The Nucleus, 2012)
Northern part of Pakistan had experienced heavy rainfall in 2010 which caused flooding in Pakistan. Statistical distributions are employed to analyze extremes of annual rainfall of different cities of KPK. Gumbel maximum and GEV distribution are used to calculate return period of extreme rainfall in different cities of Khyber Pakhtunkhwa (KPK). The analysis shows that different cities of KPK have 20-years return period for receiving more than 100 mm daily rainfall. While they have 50-years return period for receiving more than 120 mm daily rainfall.